2020
DOI: 10.3390/s20185179
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Determination of Isoprenaline in a Pharmaceutical Sample

Abstract: UV/Vis absorption spectroelectrochemistry (SEC) is a multi-response technique that has been commonly used for the characterization of materials and the study of reaction mechanisms. However, it has been scarcely used for quantitative purposes. SEC allows us to obtain two analytical signals simultaneously, yielding a dual sensor in just one experiment. In the last years, our group has developed new devices useful for analysis. In this work, a SEC device in parallel configuration, based on optical fibers fixed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Erastin could mediate ferroptosis through a variety of molecules including the cystine-glutamate transport receptor (system XC−), the voltage-dependent anion channel, and p53 (Yang et al, 2020;Liu et al, 2021). ISO, a synthetic catecholamine and nonselective β-adrenergic receptor agonist, was widely used in a reproducible and well-standardized preclinical model of cardiac remodeling and dysfunction mainly due to excess production of reactive oxygen species by persistent β-adrenergic stimulation (Olmo et al, 2020;Zeng et al, 2020). Previously, Liu et al demonstrated that ferroptosis-like cell death was observed in erastin-or ISO-treated H9c2 myocytes in vitro and in rats with aortic banding inducing HF, characterized by reduced cell viability with increased lipid peroxidation and labile iron pool (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Erastin could mediate ferroptosis through a variety of molecules including the cystine-glutamate transport receptor (system XC−), the voltage-dependent anion channel, and p53 (Yang et al, 2020;Liu et al, 2021). ISO, a synthetic catecholamine and nonselective β-adrenergic receptor agonist, was widely used in a reproducible and well-standardized preclinical model of cardiac remodeling and dysfunction mainly due to excess production of reactive oxygen species by persistent β-adrenergic stimulation (Olmo et al, 2020;Zeng et al, 2020). Previously, Liu et al demonstrated that ferroptosis-like cell death was observed in erastin-or ISO-treated H9c2 myocytes in vitro and in rats with aortic banding inducing HF, characterized by reduced cell viability with increased lipid peroxidation and labile iron pool (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…UV/Vis-SEC measurements were performed using a customized UV-VIS SPELEC instrument (Metrohm-DropSens), employing the experimental setup described previously [1,5]. A deuterium lamp was used because the reagents and products of this electrochemical process absorb electromagnetic radiation in the UV region.…”
Section: Instrumentationmentioning
confidence: 99%
“…However, it is well-known that the use of two or more techniques can be much more helpful in the determination of a molecule. Techniques such as spectroelectrochemistry (SEC) are extremely useful analytical tools in the quantification of molecules and have proven to be very useful when dealing with complex samples or when there is a large matrix effect [1][2][3][4][5]. SEC encompasses a group of analytical techniques that are characterized by the simultaneous recording of electrochemical and spectroscopic signals [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoprenaline (4-[1-hydroxy-2-[(1-methylethyl)amino]ethyl]-1,2-benzenediol), a β agonist, belongs to the catechol class of drugs and has little effect on alpha receptors6 [1]. As a potent two-point neurotransmitter, it has been used in the treatment of the neurological disorders [2].…”
Section: Introductionmentioning
confidence: 99%